Deciphering guanidine assimilation and riboswitch-based gene regulation in cyanobacteria for synthetic biology applications - M. Amadeus Itzenhäuser; Andreas M. Enkerlin; Jan A. Dewald; Bihter Avşar; Ron Stauder; Hannes Halpick; Rosalie Schaale; Lisa M. Baumann; Noelia Fernandez Merayo; Thomas Maskow; Khaled A. Selim; Christina E. Weinberg; et al. (Proceedings of the National Academy of Sciences, 2025)
Guanidine is well known as a denaturing agent. However, recent studies have demonstrated both the widespread synthesis of guanidine, e.g., in plants and mammals, as well as the widespread occurrence of guanidine metabolism in bacteria, suggesting a broader biological role. Here, we provide insights into guanidine assimilation via guanidine hydrolases (GdmH) in cyanobacteria. The gdmH gene is widespread among cyanobacteria and enables growth on guanidine as the sole nitrogen source. Consistent with this, gdmH gene expression increased under nitrogen limitation, regulated by the transcription factor NtcA. However, guanidine is toxic above 5 mM, necessitating GdmH activity and adaptive mutations activating the multidrug efflux system PrqA. The gdmH gene is frequently colocalized with ABC transporter genes (named gimABC ), which are driven by an additional NtcA-regulated promoter. The corresponding substrate-binding protein GimA showed high affinity to guanidine. Consistent with a high affinity import system, disruption of genes gimA or gimB impaired guanidine-dependent growth of Synechocystis sp. PCC 6803 at low concentrations. However, in presence of >1 mM guanidine, these mutants grew like wildtype, suggesting the existence of additional uptake mechanisms for guanidine. We also demonstrate the high-affinity binding of guanidine to a previously described, conserved RNA motif located within the gdmH 5’-untranslated region, validating it as a guanidine-I riboswitch. By combining it with various promoters, we achieved precise, titratable control of heterologous gene expression in cyanobacteria in vivo. Our findings establish guanidine assimilation as an integral element of cyanobacterial nitrogen metabolism and highlight guanidine riboswitches as valuable tools for synthetic biology.